Enhancing accurate verb usage in ESL writing through direct written corrective feedback - Muhammad Yaseen,; Mohd Hilmi Hamzah,; Minah Harun, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The scholarly discourse over the impact of corrective feedback on writing accuracy has endured for decades, ever since Truscott (2020) challenged Kang and Han’s (2015) claim about the effectiveness of direct written corrective feedback (DWCF) in enhancing learners’ grammatical writing accuracy. This study evaluated the impact of DWCF on the accurate formulation and usage of verbs in compositions written by forty English as a Second Language (ESL) learners at the Secondary School Level (SSC). The participants in the study consisted of two groups: Group A, which served as the treatment group, received DWCF treatments for twelve weeks and Group B, which served as the control group, received broad comments without any particular remedial actions. Similar levels of proficiency in verb formation and use were detected in the early tests for both groups. However, following the intervention, Group A demonstrated substantial improvements in their competency in constructing and using verbs, but Group B only exhibited minor improvements. This study contributes to the ongoing academic discourse by integrating theoretical frameworks on DWCF and demonstrating its significant and beneficial impact on enhancing verb formation and use in English language learners’ writing.